2021
DOI: 10.3390/nano11041011
|View full text |Cite
|
Sign up to set email alerts
|

ALD Deposited ZnO:Al Films on Mica for Flexible PDLC Devices

Abstract: In this work, highly conductive Al-doped ZnO (AZO) films are deposited on transparent and flexible muscovite mica substrates by using the atomic layer deposition (ALD) technique. AZO-mica structures possess high optical transmittance at visible and near-infrared spectral range and retain low electric resistivity, even after continuous bending of up to 800 cycles. Structure performances after bending tests have been supported by atomic force microscopy (AFM) analysis. Based on performed optical and electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The introduction of liquid crystal molecules into the holographic photopolymer can not only improve the refractive index modulation of the holographic photopolymer but also endow it with optical anisotropy [ 21 ]. Hence, HPDLCs have an electro-optical response and high refractive index modulation (10 −2 ) and have great application potential in high-end anti-counterfeiting, augmented reality, holographic display, and other high-tech fields [ 22 , 23 , 24 ]. However, HPDLCs suffer from insufficient stability and a mismatch between the photopolymerization reaction rate and the liquid crystal diffusion rate, which limits the performance and versatility of HPDLCs.…”
Section: Polymers For Holographic Recordingmentioning
confidence: 99%
“…The introduction of liquid crystal molecules into the holographic photopolymer can not only improve the refractive index modulation of the holographic photopolymer but also endow it with optical anisotropy [ 21 ]. Hence, HPDLCs have an electro-optical response and high refractive index modulation (10 −2 ) and have great application potential in high-end anti-counterfeiting, augmented reality, holographic display, and other high-tech fields [ 22 , 23 , 24 ]. However, HPDLCs suffer from insufficient stability and a mismatch between the photopolymerization reaction rate and the liquid crystal diffusion rate, which limits the performance and versatility of HPDLCs.…”
Section: Polymers For Holographic Recordingmentioning
confidence: 99%
“…(TCO) deposition in the aeronautic equipment [1,2]. TCO films, which combine high light transmission and electrical conductivity, are widely used [3][4][5]. However, there is generally a significant deformation mismatch between brittle TCO films and flexible polymer substrates resulting in the cracking of TCO films even at low strain [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common means to regulate the electric-optical performance is the dispersion of nanoparticles in PDLCs [25]. Many previous reports have shown that the introduction of metal, non-metal, ferroelectric, quantum dots, graphene, and other nanomaterials can lead to a notable improvement in electric-optical performance for PDLCs [26][27][28]. For example, the driving voltage of the PDLC samples can be reduced by almost 50% via doping gold nanoparticles [29].…”
Section: Introductionmentioning
confidence: 99%